Thermal behaviour of mandelic acid, sodium mandelate and its compounds with some bivalent transition metal ions - Gomes, D. J. C. [UNESP]; Caires, Flavio J. [UNESP]; Lima, L. S. [UNESP]; Gigante, A. C. [UNESP]; Ionashiro, Massao [UNESP] (Elsevier B.V., 2012)
Characterization, thermal stability and thermal decomposition of transition metal mandelates, M(C6H5CH(OH)CO2)(2) (M = Mn(II), Fe(II), Co(II), Ni(II), Cu(II), Zn(II), as well as the thermal behaviour of mandelic acid C6H5CH(OH)CO2H and its sodium salt were investigated employing simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), TG-DSC coupled to FTIR, infrared spectroscopy (FTIR), elemental analysis and complexometry. All the compounds were obtained in the anhydrous state and the thermal decomposition occurs in two or four consecutive steps. The final residue up to 320 degrees C (Mn), 345 degrees C (Fe), 400 degrees C (Co), 405 degrees C (Ni), 355 degrees C (Cu) and 575 degrees C (Zn) is Mn3O4, Fe2O3, CO3O4, NiO, CuO and ZnO, respectively. The results also provided information concerning the ligand's denticity, thermal behaviour and identification of gaseous products evolved during the thermal decomposition of these compounds. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Bivalent transition metals; Mandelate; Thermal decomposition; TG-FTIR; Evolved gases